Hubungan Tingkat Konsentrasi Pencemar Kromium Dalam Air dan Sedimen dengan Sruktur Komunitas Moluska Sungai Opak Bagian Hilir Kabupaten Bantul: The Relation of Chromium Pollutant Concentration Level in Water and Sediment toward Mollusc Community Structure in the Downstream of Opak River Bantul Regency - Ardian, Jakob (Biospecies, 2023)
The declining water quality of the Opak River, due to the heavy metal chromium, may cause disturbances to the life of aquatic biota such as mollusks. The aim of this study was to determine the relation between the concentration of chromium in the air and sediment on the mollusk community structure in the downstream of Opak River. This research was conducted in April – July 2022, in the downstream of Opak River consisting of five sampling stations (Kalasan, Piyungan, Pleret, Imogiri, Pundong) with three replications based on sampling time. The samples analyzed included samples of river water, sediment and molluscs. Analysis of the total chromium content in the sample was carried out by heating preparation at 180oC for 6 hours, then extracted by destruction method using aqua regia solution. The concentration of chromium in the sample was determined using the AAS (Atomic Absorption Spectrophotometer) method. Chromium contaminants were found in all types of samples. The highest concentration was in sediment (1,186 mg/L), followed by molluscs (0.682 mg/L) and the lowest was in water (0.124 mg/L). The types of mollusks in the downstream of Opak River are dominated by two mollusc species from the bivalves class and three mollusc species from the gastropod class with a total of 672 individuals. Corbicula javanica species became the most common mollusk with a total of 264 individuals and became the mollusk species with the highest chromium concentration of 0.914 mg/L. There was a significant relationship between the concentration of chromium in the air (p = 0.041<0.05), and sediment (p = 0.026<0.05) with the level of chromium accumulation in molluscs. Keywods: Chromium, Mollusk, Accumulation, Opak River. Abstrak Menurunnya kualitas air Sungai Opak, akibat pencemaran logam berat kromium berpotensi menimbulkan gangguan kehidupan biota perairan seperti moluska. Penelitian bertujuan untuk mengetahui hubungan antara tingkat konsentrasi pencemar kromium dalam air dan sedimen terhadap struktur komunitas moluska di Sungai Opak bagian hilir. Penelitian ini dilakukan pada April – Juli 2022, di Sungai Opak bagian hilir yang terdiri dari lima stasiun pengambilan sampel (Kalasan, Piyungan, Pleret, Imogiri, Pundong) dengan tiga replikasi berdasar waktu pengambilan sampel. Sampel yang dianalisa meliputi sampel air sungai, sedimen dan moluska. Analisis kadar kromium total pada sampel dilakukan dengan preparasi melalui pemanasan pada suhu 180oC selama 6 jam, kemudian diekstraksi dengan metode destruksi menggunakan larutan aqua regia. Konsentrasi kromium pada sampel ditentukan dengan menggunakan metode AAS (Atomic Absobtion Spectrophotometer). Pencemar kromium ditemukan pada semua jenis sampel. Konsentrasi tertinggi ditemukan pada sedimen (1,186 mg/L), kemudian diikuti moluska (0,682 mg/L) dan terendah pada air (0,124 mg/L). Jenis moluska sungai Opak bagian hilir didominasi oleh dua spesies moluska dari kelas bivalvia dan tiga spesies moluska dari kelas gastropoda dengan jumlah total sebanyak 672 individu. Spesies Corbicula javanica menjadi moluska yang paling banyak ditemukan dengan jumlah total 264 individu dan menjadi spesies moluska dengan rerata konsentrasi kromium paling tinggi yaitu 0,914 mg/L. Terdapat hubungan signifikan antara konsentrasi kromium pada air (p = 0,041<0,05), dan sedimen (p = 0,026<0,05) dengan tingkat akumulasi kromium pada moluska. Kata Kunci: Kromium, Moluska, Akumulasi, Sungai Opak